Unusual recurrent skin lesions: Bazin’s disease - Merza, Muayad A.; Adham, Dalshad K.; Yaqo, Rafil T. (International Journal Of Community Medicine And Public Health, 2019)
A 46 year old Iraqi Kurd female patient was presented with recurrent round erythematous skin lesions on her upper and lower extremities mainly calves, lower abdomen, and buttock for 3 years. Routine laboratory investigations were unremarkable; however, based on strongly positive tuberculin skin test, positive interferon gamma release assay, histo-pathological findings and a response to anti-TB treatment, she was diagnosed with Erythem Induratum of Bazin (EIB). The patient was treated successfully with combination anti-TB drugs. The skin lesions disappeared after 2 months of the treatment. There was no recurrence of the lesions over a 6 month follow up period.